1.0 GPa low carbon medium Mn heavy steel plate with excellent ductility. Issue 17 (22nd November 2019) - Chen, Jun; Ren, Jia-kuan; Liu, Zhen-yu; Wang, Guo-dong
ABSTRACT: A vanadium-bearing medium Mn heavy steel plate was designed, and the yield strength reaches around 1.0 GPa and the total elongation reaches around 18% after the annealing treatments. Meanwhile, the steel also possesses relatively good cryogenic impact toughness. Although the dislocation density of ∼2.65 × 10 14 m −2 in the hot-rolled steel decreases to ∼1.13 × 10 14 m −2 in both annealed steels and the volume fractions of retained austenite reach ∼7.9% and ∼13.5% for the steels annealed at 620°C for 1 and 2 h, there is no or small decrease in yield strength owing to numerous nanometer-sized carbides precipitated in martensite matrix. This paper is part of a Thematic Issue on Medium Manganese Steels.